(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the significance of the Russian language as a crucial tool for the development and implementation of communicative competence among physicians in the multiethnic and multilingual society of the Republic of Uzbekistan. The study emphasizes the role of interlingual medical communication in ensuring the quality of diagnostics, treatment, and medical ethics. The necessity of integrating the Russian language component into the professional training of medical university students is substantiated. The author presents recommendations for optimizing the linguistic training of future medical professionals, taking into account a practice-oriented and clinical-communicative approach.